ACORN Papua New Guinea ANGAU Memorial Hospital redevelopment clinical support program (Part 1) - Carollyn Williams; Ruth Melville; Elinor Radke; Sonia Griffiths (Journal of Perioperative Nursing)
This article is the first in a series that will describe ACORN’s role in the redevelopment of the ANGAU Memorial Hospital in Lae, Papua New Guinea.